KARAKTERISTIK ASAP CAIR DARI PROSES PIROLISIS LIMBAH SABUT KELAPA MUDA - RIKO PAMORI '; RASWEN EFENDI '; FAJAR RESTUHADI1 RESTUHADI1 ' (Jurnal Sagu, 2015)
ABSTRACTThis research aims to identify liquid smoke from young coconut fiber which containmuch water is differentfrom the others. This research was undertaken on these days in an experiment with using a Complete RandomDesign with five treatment three times repetition. Inhumanity in this research on KA1 (the level of water70%), KA2 (60%) the level of water, KA3 (the level of water 40%) KA4 (the level of water 30%) KA5 (the levelof water 20%). Parameter that observed is yield (chemistry), degrees acidity (pH), total amino tertitrasi,phenol levels, as well as the weight of. Data that was recieved by analyzed in statistics with is trial Anova. IfF count more than or equal to F table then continued with test DNMRT on a 5 percent. Results of the studyshowed that pyrolysis of young coconut fiber with the level of water 20% produce liquid smoke withcharacteristic yield (chemistry) 9.06%, the pH 2.6, the total amino 5.2%, the proportion phenol 0.660%, andthe weight of 1.009.Key words: liquid smoke, pyrolysis, young coconut fiber.